2016
DOI: 10.5812/asjsm.35024
|View full text |Cite
|
Sign up to set email alerts
|

Health Psychological Constructs as Predictors of Doping Susceptibility in Adolescent Athletes

Abstract: BackgroundDoping is a highly relevant problem in sport, even in adolescent athletes. Knowledge of the psychological factors that influence doping susceptibility in young elite athletes remains sparse.ObjectivesThis study investigated the predictive potential of different health-psychological constructs and well-being on doping susceptibility. The main hypotheses to be tested were positive associations of fear of failure, external locus of control, and ego-oriented goal orientation as well as negative associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 43 publications
1
13
0
Order By: Relevance
“…The coaches in the Nicholls et al (2015) study believed that doping susceptibility was an important construct, which was linked to doping attitudes and would influence whether or not adolescent athletes would dope, so was included in the SDCM-AA. In support of this addition, both Barkoukis et al (2014) and Blank et al (2016) reported that doping susceptibility was a proxy for doping behaviors, when it is associated with positive attitudes toward doping. To date, however, researchers have assumed a concomitant relationship between doping susceptibility and doping behavior, without assessing this directly.…”
Section: The Sport Drug Control Model For Adolescent Athletesmentioning
confidence: 74%
See 1 more Smart Citation
“…The coaches in the Nicholls et al (2015) study believed that doping susceptibility was an important construct, which was linked to doping attitudes and would influence whether or not adolescent athletes would dope, so was included in the SDCM-AA. In support of this addition, both Barkoukis et al (2014) and Blank et al (2016) reported that doping susceptibility was a proxy for doping behaviors, when it is associated with positive attitudes toward doping. To date, however, researchers have assumed a concomitant relationship between doping susceptibility and doping behavior, without assessing this directly.…”
Section: The Sport Drug Control Model For Adolescent Athletesmentioning
confidence: 74%
“…It is unknown why these athletes chose not to participate in this research, and this could raise issues regarding the validity of the data. The response rate of 88% compares favorably to other studies examining the psycho-social factors associated with doping, such as Giraldi et al (2015) who reported a response rate of 76.91%, but inferior to other research with response rates of 100% (Blank et al, 2016) and 95% (Mudrak et al, 2018). Although the sample contained more athletes from the United Kingdom, unlike many studies within the doping literature, our study includes athletes from multiple countries and across four continents.…”
Section: Limitationsmentioning
confidence: 80%
“…Literature has suggested that chronic stress leads to depression ( Risch et al, 2009 ), increasing hopelessness and suicidal ideation ( Glick et al, 2012 ). Furthermore, it has been found that depressed adolescent athletes are susceptible to doping ( Blank et al, 2016 ). Therefore, future studies should examine how athletes’ personal maladjustment and desire for change influence unhealthy behaviors, motivations, and overall well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Factors such as high drive for muscularity or muscle dysmorphia (Jampel, Murray, Griffiths, & Blashill, 2016;, holding masculine values (Keane, 2005), valuing traditional male roles (Kanayama, Barry, Hudson, & Pope, 2006) and low levels of self-esteem (Blank, Schobersberger, Leichtfried, & Duschek, 2016;Nicholls et al, 2014) have been associated with increased likelihood of AAS use. Other personal factors identified include a history of abuse or bullying (Dennington, Dillon, Finney Lamb, & Larance, 2008;Petrocelli, Oberweis, & Petrocelli, 2008), the tendency for risk taking behaviors (DuRant, Escobedo, & Heath, 1995;Pedersen & Wichstrøm, 2001) and moral disengagement (Judge et al, 2012;Mallia et al, 2016).…”
Section: Individual Levelmentioning
confidence: 99%